Impact of co-morbidities on health-related quality of life 10 years after surgical treatment of oesophageal cancer. Issue 4 (29th May 2020) - Klevebro, F; Johar, A; Lagergren, P
Abstract: Background: Oesophagectomy for cancer is associated with long-term decreased health-related quality of life (HRQoL). The aim of this study was to evaluate the effect of co-morbidities on HRQoL among survivors of oesophageal or gastro-oesophageal junctional cancers after 10 years or more. Methods: The study included a prospectively collected, population-based cohort, comprising all patients who had surgery for oesophageal or gastro-oesophageal junctional cancer in Sweden in 2001–2005 with follow-up until 31 December 2016. All data regarding patient and tumour characteristics, treatment details and HRQoL were collected using a prospectively created database. Multivariable ANCOVA regression models, adjusting for age, sex, tumour histology, stage and surgical technique, were used to calculate adjusted mean scores with 95 per cent confidence intervals for all HRQoL outcomes. Results: A total of 92 survivors (88·5 per cent) responded to the questionnaires. Patients were stratified in two groups according to whether they reported a low or high impact of co-morbidities on general health. Patients in the high-impact group had clinically significantly decreased HRQoL and an increased level of symptoms, but differences between these two groups were not statistically significant. Conclusion: Co-morbidities with high impact on general health still contribute to impaired HRQoL 10 years after oesophagectomy for cancer. Graphical Abstract: This study investigated the impact of co-morbidities on health-related quality of life during long-term follow-up after oesophagectomy. The results showed that the substantial impact of co-morbidities on reported general health might be associated with symptoms and health-related quality of life 10 years after oesophageal cancer treatment. Co-morbidities affect long-term QOL.